use strict;
my $str = '2H2 + O2 -> 2H2O; k1*H2*H2*O2
C + O2 -> CO2; k2*C*O2';
my $regex = qr/^[0-9]* *([a-zA-Z]+[0-9]*)+( *\+ *[0-9]*([a-zA-Z]{1,2}[0-9]*))* *-> *[0-9]* *([a-zA-Z]+[0-9]*)+( *\+ *[0-9]*([a-zA-Z]{1,2}[0-9]*))* *; *[a-z][0-9]+( *\* *[0-9]*([a-zA-Z]{1,2}[0-9]*))*$/mp;
my $subst = '';
my $result = $str =~ s/$regex/$subst/rg;
print "The result of the substitution is' $result\n";
Please keep in mind that these code samples are automatically generated and are not guaranteed to work. If you find any syntax errors, feel free to submit a bug report. For a full regex reference for Perl, please visit: http://perldoc.perl.org/perlre.html